Experimental investigation on emission characteristics of non-road diesel engine equipped with integrated DOC + CDPF + SCR aftertreatment. (1st December 2021) - Hu, Jie; Liao, Jianxiong; Hu, Youyao; Lei, Jun; Zhang, Ming; Zhong, Jing; Yan, Fuwu; Cai, Zhizhou
Highlights: The effects of integrated DOC + CDPF + SCR aftertreatment on engine emission characteristics were investigated under different operations. The engine emission factors lower than non-road China-IV emission limits (NRSC) could be achieved via DOC + CDPF + SCR under all test operations except for 10% load. The high efficiencies of filtering PM and PN via DOC + CDPF + SCR were greatly affected under neither transient cycle nor steady operations. The reduction excellency of this aftertreatment makes it possible to offer a practical solution for non-road emission improvement without any engine modification. Abstract: The non-road emission regulations are getting more and more rigorous, which make it necessary for Original Equipment Manufacturers (OEMs) to adopt aftertreatment systems. In this paper, an integrated aftertreatment system consisting of Diesel Oxidation Catalyst (DOC), Catalytic Diesel Particulate Filter (CDPF) and Selective Catalytic Reduction (SCR) was proposed aiming to reduction of non-road diesel engine emissions. The effects of DOC + CDPF + SCR on engine performance and emission characteristics including HC, CO, NOX, PM, PN and NH3 slip were investigated under steady operations and transient cycle. The results showed that DOC + CDPF + SCR had little influence on engine power and economic performance. In initial DOC reduced HC and CO emissions by the efficiency of 89% and 91% respectively, CDPF dealt with the remained inheritance of HC and CO by 75% and 80% respectively latterly. The DOC + CDPF specifically raised the ratio of NO2 /NOx although there was barely the influence on NOx emission. The efficiencies of DOC + CDPF filtering PM and PN were over 95%, and CDPF had better performance of filtering accumulation particles than it applied on nuclear particles. SCR NOx reduction efficiency was 90% and ammonia slip was 14 ppm on average. The emissions factors of CO, HC, NOx, PN and PM, lower than non-road China-IV limits of non-road steady cycle (NRSC) under all test operations except for 10% load, due to the equipped integrated DOC + CDPF + SCR aftertreatment, decreased by 97.6%, 98.1%, 90%, 97% and 98% respectively. In the whole hot non-road transient cycle (NRTC), HC and CO reduction efficiencies were 57.1% and 55% in average in DOC. In addition, the efficiencies of 68.3% and 19.8% could be further achieved in CDPF respectively in average. It is especially important that CDPF-out NO2 /NOx ratio fluctuated and did increase at some special time due to the lack of adequate PM and NO2 reaction time in transient cycle although CDPF-out NO2 /NOx ratio decreased under steady operations. The SCR NOx reduction in average was 57.7% and ammonia slip was less than 10 ppm. PM and PN diminished by 95% and 98.3% respectively in the DOC + CDPF and the transient operation fluctuation had little effect on filtration efficiency.